Upaya Guru Dalam Membentuk Akhlak Peserta Didik - Gifa Oktavia; Afifah Febriani; Anita Sepriasa (Murabby: Jurnal Pendidikan Islam, 2023)
This research aims to determine the efforts made by teachers in shaping students' morals. This research uses qualitative methods with a case study approach (case study design). Data sources were taken from seven informants using an interview protocol. The interview results were analyzed thematically using Miles and Huberman. Overall the results show that there are three efforts made by teachers to shape students' morals. The three efforts are i) being a role model, ii) giving advice and iii) giving sanctions. This research has succeeded in revealing the efforts made by teachers in shaping students' morals. The results of this research can be used as initial data for subsequent research in studying this problem in different contexts and issues.